Discover the best answers to your questions with the help of IDNLearn.com. Discover detailed answers to your questions with our extensive database of expert knowledge.

Which algebraic properties was applied to the expression a + (b + c) = (a + b) + c?

Sagot :

Answer:

the Associative Property

Step-by-step explanation:

Notice that the ORDER doesn't change -- a, b, c on both sides.  But the GROUPING changes.

Example:

3 + (4 + 5) = (3 + 4) + 5

3 + 9 = 7 + 5

12 = 12

Subtraction does NOT behave this way!

8 - (7 - 1) = 8 - 6 = 2

(8 - 7) - 1 = 1 - 1 = 0

It matters who you associate with!  :-)